Stereo vision based robotic bin picking system for agile manufacturing - Fathinul-Syahir, Ahmad Sa'ad; Hazry, Desa, Dr.; Muhammad Juhairi Aziz, Safar (Universiti Teknologi Malaysia (UTM), 2011)
Organized by Faculty of Electrical Engineering, Universiti Teknologi Malaysia (UTM), 2nd - 3rd June 2009 at Malacca, Malaysia.